2017
DOI: 10.1177/1420326x17700948
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of indoor air quality at urban schools in Qatar

Abstract: Information about indoor conditions of classrooms in Qatari schools is very scarce and availability of indoor air quality (IAQ) data is important as children are vulnerable to health hazards and spend long times in classrooms. Therefore, IAQ was investigated in 16 mechanically ventilated schools in Qatar during the winter season. Parameters such as temperature, relative humidity, carbon monoxide (CO), carbon dioxide (CO2) and particulate matters (PM10 and PM2.5) were measured indoors and outdoors simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Over the years, several studies have been conducted with the aim of understanding indoor air quality of school environment across the world [11][12][13][14][15][16][17][18][19][20][21][22][23]26,[52][53][54][56][57][58][59][60][61][62][63]. In a study, Tippayawong et al [62] found that the highest concentrations were measured for particles in the 0.3 -0.5 μm size range with an average value of 180 cm -3 while the lowest concentrations were measured in the 2.5 -5 μm size range with an average of 0.05 cm -3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, several studies have been conducted with the aim of understanding indoor air quality of school environment across the world [11][12][13][14][15][16][17][18][19][20][21][22][23]26,[52][53][54][56][57][58][59][60][61][62][63]. In a study, Tippayawong et al [62] found that the highest concentrations were measured for particles in the 0.3 -0.5 μm size range with an average value of 180 cm -3 while the lowest concentrations were measured in the 2.5 -5 μm size range with an average of 0.05 cm -3 .…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, several research work has been published with respect to IAQ in schools in both developed and developing countries around the world [11][12][13][14][15][16][17][18][19][20][21][22][23]. Some of the human health implications associated with PM pollutions in schools are as follows: higher susceptibility of children to environmental pollutants [24,25,26], higher inhalation rates per body mass [27,28], and longer time spent in schools [26,28]. Findings from several studies have identified different pollutant parameters that contribute to IAQ problems in some schools around the world.…”
Section: Journal Of Environment Pollution and Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…High indoor concentrations of 3442 ± 1710 mg/m 3 , 93.2 ± 42.4 μg/m 3 , and 60.1 ± 28.8 μg/m 3 were observed for CO 2 , PM 10 , and PM 2.5 , respectively. These exposure levels exceeded the international threshold limits (Table 2) as Qatar currently does not have IAQ standards (Abdel-Salam, 2017). In 2018, 24-h measurements of pupil's exposure to PM 2.5 , VOC, PAHs, and aldehydes were conducted in three classrooms, pupils' homes, and outdoor environments in Doha.…”
Section: Air Pollutants In Qatarmentioning
confidence: 99%
“…Hence, indoor air pollution poses a health threat to Qatari residents even in a building, where no major activities occur (e.g., smoke-free) (Al Mulla et al, 2015). This implies that infiltration from outdoor sources, mostly from dust storms, heavy traffic emissions, and industrial activities are the principal sources of indoor air pollution in Qatar (Abdel-Salam, 2017;Alfoldy, 2018).…”
Section: Air Pollutants In Qatarmentioning
confidence: 99%